2008
DOI: 10.2459/jcm.0b013e3282f03b90
|View full text |Cite
|
Sign up to set email alerts
|

Women and peripheral arterial disease: same disease, different issues

Abstract: In PAD, there are several sex differences in baseline characteristics, especially with respect to the weight and significance of cardiovascular risk factors. Knowledge of these differences may help achieve optimal gender-specific cardiovascular risk prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Older studies have shown that women with PAD tend to be older and have dyslipidemias more often than men [8,9]. In our cohort this was true regarding total cholesterol values, which were significantly higher on admission than those of men, whereas HDL-cholesterol was lower.…”
Section: Discussionsupporting
confidence: 57%
“…Older studies have shown that women with PAD tend to be older and have dyslipidemias more often than men [8,9]. In our cohort this was true regarding total cholesterol values, which were significantly higher on admission than those of men, whereas HDL-cholesterol was lower.…”
Section: Discussionsupporting
confidence: 57%
“…4144 Using the SF‐36, previous authors have demonstrated that physical functioning and general health were both significantly lower for women, 14 which was consequently associated with greater mood disturbance than in men with PAD. 13 In addition, female gender adversely impacts durability or quality of life following revascularization for claudication or critical limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our study are in line with previous research suggesting that women with PAD have a worse health status and health-related quality of life as compared with men, 9,[13][14][15]40 and contrasts with those that have found no differences by gender. [41][42][43][44] Using the SF-36, previous authors have demonstrated that physical functioning and general health were both significantly lower for women, 14 which was consequently associated with greater mood disturbance than in men with PAD. 13 In addition, female gender adversely impacts durability or quality of life following revascularization for claudication or critical limb ischemia.…”
Section: Symptomatic Health Statusmentioning
confidence: 99%
“…100 Studies differ on whether the prevalence of PAD in nondiabetic individuals is greater in women or men, 101,102 but women tend to develop PAD at an older age. 103 The prevalence of PAD in female versus male patients with DM has not been clearly established. 100 In both sexes, there is a substantial overlap between PAD with CHD and cerebrovascular disease, as would be expected, and PAD is considered a CHD risk equivalent.…”
Section: Sex Differences In Peripheralmentioning
confidence: 99%